Spondyloarthritis: Pathogenesis, Clinical Manifestations, Diagnosis, and Management - Pilar S. del Río-Martínez (European Medical Journal, 2016)
The term spondyloarthritis (SpA) is used to describe a heterogeneous group of diseases sharing certain characteristics. Traditionally, patients with SpA have been classified in five subgroups: ankylosing spondylitis (AS), psoriatic arthritis, arthritis associated with inflammatory bowel disease (IBD), reactive arthritis, and undifferentiated SpA. The pathogenesis of SpA is still not entirely clear; it is considered to be multifactorial, the result of interaction between genetic risk factors and environmental triggers that lead to activation of autoinflammation and autoimmunity. This group of diseases is characterised by a chronic inflammation in entheses and other anatomical structures, leading to their main clinical features: sacroilitis, enthesitis, and peripheral arthritis. An association with extra-articular manifestations such as psoriasis, uveitis, and IBD is also a distinctive feature of SpA. Several diagnostic and classification criteria have been proposed over time. However, all of these criteria have a main limitation, which is the difficulty to identify patients at an early stage of the disease. The Assessment of Spondyloarthritis International Society (ASAS) proposed the ASAS classification criteria that introduced two major changes: first, the classification of patients with SpA based on the predominant symptoms (axial or peripheral); second, the introduction of magnetic resonance imaging, which allows detection of sacroiliitis at the early stages of the disease. Nowadays, the ASAS criteria classify SpA in two groups: axial SpA, including classical AS and non-radiographic axial SpA, and peripheral SpA. The therapy for SpA has evolved dramatically over time. The introduction of biological therapy in recent years, which has continuously progressed, has improved the functional and clinical prognosis of SpA patients.